2017
DOI: 10.1371/journal.pone.0177679
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction increase the expression of mTORC1 complex genes in the skeletal muscle of juvenile pacu (Piaractus mesopotamicus)

Abstract: Skeletal muscle is capable of phenotypic adaptation to environmental factors, such as nutrient availability, by altering the balance between muscle catabolism and anabolism that in turn coordinates muscle growth. Small noncoding RNAs, known as microRNAs (miRNAs), repress the expression of target mRNAs, and many studies have demonstrated that miRNAs regulate the mRNAs of catabolic and anabolic genes. We evaluated muscle morphology, gene expression of components involved in catabolism, anabolism and energetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 82 publications
7
26
0
1
Order By: Relevance
“…The pacu ( Piaractus mesopotamicus ), which is characterized by hardiness, fast growth, adaptation to artificial feeding and flavorsome meat (Castagnolli and Cyrino, 1986 ), is a valuable resource in Brazilian aquaculture (Urbinati and Gonçalves, 2005 ). Duran et al ( 2015 ) and Paula et al ( 2017 ) studied the role of skeletal muscle miRNAs in this Neotropical fish during development and under food restriction, respectively. Duran et al ( 2015 ) analyzed the impact of the miRNA-target interactions of miR-1/ hdac4 , miR-133-a/b/ srf , miR-206/ pax7 , and miR-499/ sox6 in fast- and slow-twitch skeletal muscles during growth.…”
Section: A Review Of Mirnas In Farmed Fishesmentioning
confidence: 99%
“…The pacu ( Piaractus mesopotamicus ), which is characterized by hardiness, fast growth, adaptation to artificial feeding and flavorsome meat (Castagnolli and Cyrino, 1986 ), is a valuable resource in Brazilian aquaculture (Urbinati and Gonçalves, 2005 ). Duran et al ( 2015 ) and Paula et al ( 2017 ) studied the role of skeletal muscle miRNAs in this Neotropical fish during development and under food restriction, respectively. Duran et al ( 2015 ) analyzed the impact of the miRNA-target interactions of miR-1/ hdac4 , miR-133-a/b/ srf , miR-206/ pax7 , and miR-499/ sox6 in fast- and slow-twitch skeletal muscles during growth.…”
Section: A Review Of Mirnas In Farmed Fishesmentioning
confidence: 99%
“…Previous studies in our group have also analyzed the function of some miRNAs in the skeletal muscle of sh involving fasting and re-feeding treatments and muscle development [16], [17]. The authors observed that some miRNAs (miR-1, miR-133, miR-155, miR-206, and miR-499) presented a possible role in the regulation of factors related to muscle cell proliferation and differentiation and with muscle performance and metabolism, modulating the rate of protein synthesis and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary histidine requirement of grow-out Nile tilapia (Oreochromis niloticus), based on growth performance... Zaminhan-Hassemer et al Fish recruits new muscle fibers throughout their lifetime (Rowlerson and Veggetti, 2001), and hypertrophic and hyperplasic muscle growth may be influenced by nutrition (Dal Pai et al, 2000). Genomics assays have been used to better understand how nutrients can affect muscle-growth-related genes and metabolic responses in fish (Alami-Durante et al, 2010;De Paula et al, 2017). Muscle growth processes are regulated by the activation and proliferation of satellite cells and myogenic regulatory factors (MRF), such as MyoD and myogenin, and MyoD regulates myogenic activity in cell differentiation (Watabe, 1999).…”
Section: Introductionmentioning
confidence: 99%